The role of vascularized flaps in the treatment of proximal pole avascular necrosis in scaphoid non-unions - Guzzini, Matteo; Lanzetti, Riccardo Maria; Proietti, Lorenzo; Lupariello, Domenico; Iorio, Raffaele; Ferretti, Andrea (Acta Biomedica Atenei Parmensis, 2019)
Objectives: The purpose of this study is to evaluate the clinical and radiological outcomes of scaphoid non unions surgically treated with bone graft versus medial condyle corticoperiosteal free flaps. Materials and Methods: 32 patients were divided in 2 groups. Group A (17 patients 12male, 5 females, mean age 35 years old) treated with bone grafts; Group B (15patients 11 male, 4 females, mean age 33 years old) treated with medial condyle cortico periosteal free flap. A radiological follow up was performed about every 30 days after surgery until the complete healing and at 12-month follow-up. The clinical follow up was performed at 6 and 12 months from surgery. Functional assessment was provided by Mayo wrist score and Visual Analogic Scale (VAS). Results: The average length of follow up was 12.52 months ± 1.36. In group A 60% of patients healed in 4.4 ± 1months with a reduction of 28.4% of healing times in group B (p<0.05).In Group B all nonunion sites healed primarily at an average time period of 3.2 ± 1 months. Statistical analysis showed a significant difference (p<0.001) about the preoperative and the postoperative VAS and Mayo Wrist Score evaluation in both groups at 6 and 12-month follow-up, moreover we recorded a statistical difference between groups at the 6-month and 12-month follow-up (p<0.05). Conclusion: The present study showed that the free flaps showed better clinical and radiographic results for the surgical treatment of scaphoid nonunions. In fact, despite the good results of the bone graft, the flaps seems to be preferable in the treatment of these nonunions.